Metabolomics Insights into Salivary Profile in Dogs with Babesia canis Infection - Josipa Kuleš; Ivana Rubić; Dina Rešetar Maslov; Maša Efendić; Krešimir Martinković; Elizabeta Pongrac; Iva Šmit; Dalibor Potočnjak; Renata Barić Rafaj; Vladimir Mrljak (Biomolecules)
Babesiosis is a significant vector-borne zoonotic disease with major global economic and health implications, affecting various vertebrate hosts. Babesia parasites are auxotrophic for essential nutrients, relying on their hosts for metabolic support. This study investigated salivary metabolomic changes in dogs naturally infected with Babesia canis (N = 14) compared to healthy controls (N = 14) using untargeted and targeted mass spectrometry-based approaches. Saliva, a biofluid rich in metabolites, undergoes alterations in response to systemic diseases, making it a promising medium for studying host–pathogen interactions. Metabolomic profiling was performed using a Dionex UltiMate 3000 UHPLC system coupled with a Thermo Orbitrap Q Exactive mass spectrometer. An untargeted analysis detected 2257 salivary features, of which, 868 were significantly altered, with seven metabolites identified by reference to standards. A targeted analysis revealed significant changes in seven metabolites. Functional bioinformatics indicated disruptions in amino acid, nucleotide, and lipid metabolism, alongside alterations in energy production pathways, and purine metabolism. These findings provide critical insights into the metabolic shifts underlying canine babesiosis, supporting the development of advanced diagnostic and therapeutic strategies in the future. This study highlights the intricate interplay between host and pathogen, particularly in nutrient acquisition and metabolic regulation.